Induction thermography: principle, applications and first steps towards standardisation. Issue 2 (2nd July 2016) - Netzelmann, Udo; Walle, Günter; Lugin, Sergey; Ehlen, Andreas; Bessert, Steffen; Valeske, Bernd
Abstract: A survey on theory, characteristic quantities and the experimental technique of induction thermography is given. Induction thermography is used for surface defect detection in forged parts of ferromagnetic steel at typical frequencies of 100–300 kHz. The sensitivity for crack detection is comparable to magnetic particle inspection. A hidden defect in ferritic steel with a coverage of 140 μm was detected by lowering the induction frequency down to 1500 Hz. Defects of fibres were detected in carbon fibre reinforced polymer (CFRP). Inductive excitation is complementary to flash excitation. By increasing the induction frequency up to 52 MHz, surface heating of CFRP can be realised. Cracks in silicon solar cells were detected. The crack tip is revealed with very high contrast. A new field is crack detection in railway components like rails and wheels. In rails, a larger defect could be detected from a test car moving at a speed of up to 15 km/h. A fully automated wheel testing system was built up as a demonstrator, that can detect defects with comparable sensitivity to magnetic particle testing. Standardisation of thermography has gained progress in the last years and will lead to standards on active thermography, flash excited and induction thermography in the next future.